The Influence of Dexamethasone with Lidocaine Hydrochloride Iontophoresis in Recreational Tennis Players Suffering from Lateral Elbow Tendinopathy - Stergioulas Apostolos; Sotiropoulos Dimosthenis; Stasinopoulos Dimitrios (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2014)
Background: Lateral elbow tendinopathy (LET) is a common clinical condition of the upper limp. Many treatments, medical and physical therapy, has been recommended for the management of LET. One of these recommended treatments is iontophoresis.  Objective: The aim of the present study was to determine the effects of iontophoresis using a combination of dexamethasone with lidocaine hydrochloride in the treatment of LET in recreational tennis players. Methods: A Controlled clinical trial in the Physiotherapy Department of Panarkadikon hospital was conducted. Sixty eight patients who had LET for at least four weeks participated in the study. They were allocated to two groups by alternative allocation. Group A (n=35) received iontophoresis with dexamethasone and lidocaine hydrochloride and Group B (n=33) was treated with placebo iontophoresis. All patients received two treatments per week for six weeks. Pain, range of motion, pain free grip strength and function were evaluated at baseline, at the end of treatment and one month after the end of the treatment. Results: A significant decrease in pain intensity in the iontophoresis group at the end of treatment and at one-month follow-up (p<0.01, p< 0.001), compared with pretreatment values. Pretreatment values were also significantly lower than in the control group at the same time periods (<0.01, p<0.001), pain free grip strength (p<0.05 and p<0.01, respectively) and function (p<0. 05 and p<0. 05 respectively) of the iontophoresis group increased significantly at the end of the treatment and at the follow up. Pretreatment values were also significantly lower than in the control group at the same time periods (p<0.05, p<0.01).  Conclusions: The solution of dexamethasone with lidocaine hydrochloride iontophoresis has positive effects in the treatment of LET in recreational tennis players. Further research is needed to confirm our results.